Balanço de energia de fluxo de CO2: cerrado da floresta estadual de Assis - Fernandes, Edson Xavier [UNESP] (2014)
Based on climatological data and energy flow, this paper analyzes the behavior observed in microclimatic an important remnant of cerrado in the São Paulo State. The seasonal climate is well marked, in the study area, with two climatic periods (one dry and one wet). The vegetation presents physiology as a function of water availability and the local thermal conditions and can be seen marked changes in the landscape due to the more or less presence of solar radiation. It’s important to understand the ecosystems behave in the context of global change. It has gained the attention of many researchers in the world.